Application of the Discovery Learning Model for Physical Education Teachers - Fitri Agung Nanda; Hartati Hartati; Wahyu Indra Bayu; Soleh Solahuddin; Arif Hidayat; Alvin Anggara (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to provide information and guidance to Physical Education, Sports, and Health (PJOK) teachers in Indralaya, Ogan Ilir, regarding the application of the discovery learning model in the PJOK learning process. The partner for this activity is the Indralaya PJOK Subject Teacher Working Group (MGMP), comprising 40 teachers. The method was carried out with a participatory approach through outreach, workshops, and practical training accompanied by mentoring. This program aims to improve the competence of Physical Education, Sports, and Health teachers in implementing the discovery learning model that aligns with the principles of student-centered learning in the independent curriculum. Pre-test and post-test data were analyzed descriptively and quantitatively by comparing the average scores before and after the activity, while teacher reflection data were analyzed descriptively and qualitatively to strengthen the interpretation of the quantitative results. The results of the activity showed that before the socialization, 63.6% of teachers did not fully understand the discovery learning model, and only 36.4% had tried to apply it, although they still experienced difficulties in implementing the learning project. After the dissemination and guidance activities, the teachers' understanding increased significantly, with 100% of participants stating that they understood and were able to apply the discovery learning concept in PJOK learning. This activity had a positive impact on improving the pedagogical competence of PJOK teachers in Indralaya Ogan Ilir, particularly in the application of innovative learning models to improve the quality of student learning outcomes.